1995
DOI: 10.2337/diab.44.11.1285
|View full text |Cite
|
Sign up to set email alerts
|

Phosphofructokinase Isozymes in Pancreatic Islets and Clonal β-Cells (INS-1)

Abstract: Normal insulin secretion is oscillatory in vivo, and the oscillations are impaired in type II diabetes. We and others have shown oscillations in insulin secretion from isolated perifused islets stimulated with glucose, and in this study we show oscillations in insulin secretion from the glucose-sensitive clonal beta-cell line INS-1. We have proposed that the oscillatory insulin secretion may be caused by spontaneous oscillations of glycolysis and the ATP:ADP ratio in the beta-cell, analogous to those seen in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 0 publications
1
58
0
Order By: Relevance
“…The burst is terminated once the supply of high-energy phosphate donors is exhausted, allowing the ATP/ADP ratio to decay (83). Supporting the idea that glycolysis may oscillate is the presence of PFK-M, the PFK isoform with known oscillatory behavior, in islets (84). Interestingly, mutations in this enzyme are associated with impairment of oscillatory insulin release in humans (85).…”
Section: Inherent Glycolytic Oscillationsmentioning
confidence: 74%
“…The burst is terminated once the supply of high-energy phosphate donors is exhausted, allowing the ATP/ADP ratio to decay (83). Supporting the idea that glycolysis may oscillate is the presence of PFK-M, the PFK isoform with known oscillatory behavior, in islets (84). Interestingly, mutations in this enzyme are associated with impairment of oscillatory insulin release in humans (85).…”
Section: Inherent Glycolytic Oscillationsmentioning
confidence: 74%
“…These oscillations are driven by autocatalytic activation of the muscle isoform of the key glycolytic enzyme phosphofructokinase-1 (PFK-1) by its product fructose 1,6-bisphosphate resulting in large oscillations in the ATP:ADP ratio. The muscle isoform of this enzyme, PFK-M, has recently been shown to be the dominant PFK activity in beta cells [61].…”
Section: Oscillations In Insulin Secretionmentioning
confidence: 99%
“…Concerning insulin secretion of the pancreatic ␤ cell (17), a coincidence between reduced PFK1 activity and impaired insulin secretion has been described in vitro (18,19), but was explained by primary phosphate depletion and consequently impaired secretion in the particular experimental setup used. Recently, Yaney and coworkers (20) demonstrated the presence of all three isotypes of PFK1 in rat-derived ␤ cell lines and islets at the protein level. In an extensive investigation of the complex regulation of the enzyme, negative by both ATP and citrate, and autocatalytically positive by AMP-dependent activation by fructose-1,6-bisphosphate, they concluded that PFK1-M contributed most of the activity under physiological intracellular conditions.…”
Section: Introductionmentioning
confidence: 99%